Parental attachment style and severity of emotional/behavioral problems in toddlerhood [Ebeveynin romantik baǧlanma stili ile erken çocukluk döneminde sosyal duygusal sorun düzeyi] - (:unkn) unknown (Turkish Neuropsychiatric Society, 2011)
Objective: We aimed to investigate the association between maternal and paternal attachment style and severity of emotional and behavioral problem severity in toddlers and to explore the effect of toddlers' gender, presence of autism, and parental depression on this relation. Methods: All patients (n=103) (male=75; female=28) younger than 43 months old (range: 14-43, mean: 30.93±8.26 months) were included from a clinical sample. The Structured Clinical Interview for DSM-IV-TR, Beck Depression Inventory, and Adult Attachment Scale (AAS) were used for assessing mothers and fathers; the Child Behavior Checklist/ 2-3 (CBCL) and Aberrant Behavior Checklist (ABC) were applied to evaluate associated psychopathology in toddlers. Results: Both maternal and paternal AAS-avoidance scores were found to be significantly correlated with ABC-hyperactivity and ABC-irritability scores of the toddler (p<.001). A multiple regression model significantly predicted ABChyperactivity scores, F(4.47)=5.74, p<.001, with two variables (higher paternal BDI score, and maternal insecure attachment style) significantly contributing to the prediction. Conclusion: The overall results of this study indicate that maternal (but not paternal) insecure attachment style is significantly associated with the severity of toddlers' emotional and behavioral problems, such as hyperactivity, and irritability. Especially when combined with paternal depression, this association becomes stronger. © Archives of Neuropsychiatry, published by Galenos Publishing.
Keywords: Attachment; Father-infant interaction; Mother-infant interaction